Conferencia continental por la paz y la soberania en Centroamerica y el Caribe (CONIPAZ (Comite Nicaraguense por la Paz), 1983)
Banner streaming out of Central America on a globe Poster advertising conference on Latin American countries' liberation, held in Managua, 1983 PO-1667